Schism in pentecostal churches: a case of Apostolic Faith Mission (AFM) in Zimbabwe (2008-2017 - Musariri, John (Midlands State University, 2018)
This research emphasises on the causes of schisms in Pentecostal Churches with particular reference to AFM in Zimbabwe church from 2008-2017. This is as a result of continuous emergence of Pentecostal churches through splits from AFM and other old Pentecostal churches. There is also a rapid increase in Pentecostal churches for the past decade. Despite challenges it faced, AFM continued to grow in areas such as numerical, spiritual, infrastructural, political and technological. There are a lot of causes of these schisms which include economic challenges, doctrinal differences, spiritual gifts, leadership and management, technology and others. They affect the churches both negatively and positively. Schisms cause destruction of relationships, retardation in church growth, destruction of the church’s reputation, destruction in people’s faith and others. On the other hand, they help to expand the kingdom of God. Whenever necessary the churches are encouraged to maintain unity.